2023
DOI: 10.1159/000528989
|View full text |Cite
|
Sign up to set email alerts
|

How Surgical Research Gave Birth to a New Clinical Surgical Field: A Viewpoint from the Dallas Uterus Transplant Study

Abstract: Background: Uterus transplantation (UTx) has come of age in the 21st Century, building on the 20th Century developments in vascular anastomosis and effective immunosuppressive protocols enabling solid organ transplantation to become the life extending and life improving treatment option we know today. However, UTx has the goal of enabling reproduction, meaning that research focused on establishment of pregnancy and healthy live birth in addition to surgical technique and immunosuppression. Summary: The Dallas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…However, an open procedure has a higher incidence of postoperative surgical complications and graft failure [27]. A total of 59 living-donor hysterectomies have been reported in the literature (Table 1), including 35 performed with a laparotomic approach, 20 with a robotic approach and 4 with a laparoscopic approach [6,15,16,20,22,[44][45][46][47][48][49][50][51][52][53][54][55][56][57]. The mean donor age was 45.6 ± 9.1 years, and 22 were unrelated with the recipients, 34 were emotionally related (27 mothers, 5 sisters, 2 mother's sisters), while in three cases, the relationship was not reported.…”
Section: Surgical Issues Of Uterus Transplantation 41 Living Donormentioning
confidence: 99%
See 1 more Smart Citation
“…However, an open procedure has a higher incidence of postoperative surgical complications and graft failure [27]. A total of 59 living-donor hysterectomies have been reported in the literature (Table 1), including 35 performed with a laparotomic approach, 20 with a robotic approach and 4 with a laparoscopic approach [6,15,16,20,22,[44][45][46][47][48][49][50][51][52][53][54][55][56][57]. The mean donor age was 45.6 ± 9.1 years, and 22 were unrelated with the recipients, 34 were emotionally related (27 mothers, 5 sisters, 2 mother's sisters), while in three cases, the relationship was not reported.…”
Section: Surgical Issues Of Uterus Transplantation 41 Living Donormentioning
confidence: 99%
“…The mean donor age was 45.6 ± 9.1 years, and 22 were unrelated with the recipients, 34 were emotionally related (27 mothers, 5 sisters, 2 mother's sisters), while in three cases, the relationship was not reported. The mean recipient age was 28.8 ± 4.5 years, and the MRKH syndrome was the most common indication for uterus transplant (52 patients), while 2 patients required UTx after hysterectomy for myomectomy and 1 patient following hysterectomy for cervical cancer [6,15,16,20,22,[44][45][46][47][48][49][50][51][52][53][54][55][56][57]. With the open technique, a subumbilical midline incision is used while five working ports are used in robotics.…”
Section: Surgical Issues Of Uterus Transplantation 41 Living Donormentioning
confidence: 99%
“…Advances in surgical techniques and technology have contributed to developing and improving UTx procedures. For example, robotic-assisted surgery has been introduced to reduce operative time for donors and recipients [ 21 , 32 ]. Additionally, studies in cynomolgus macaques have demonstrated that using ovarian veins reduced the operative time for living donors [ 33 ].…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, advances in immunosuppressive therapy have improved the success rates of UTx procedures, reducing the risk of transplant rejection. The use of IVF has also been introduced to achieve pregnancy after UTx [ 32 ]. Overall, advances in surgical techniques and technology have contributed to the development and improvement of UTx procedures, reducing the risks and complications associated with the surgery and improving the success rates of the procedure.…”
Section: Reviewmentioning
confidence: 99%
“…As UTx transitions from experimental to clinical practice [ 9 ], it is important to assess how well the population ultimately interested in undergoing the procedure matches the population for which safety and effectiveness data have been established. Both technical and ethical considerations for UTx may differ by recipient characteristics, such as the cause of infertility and parity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%